Pengaruh Promosi, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Hoka-Hoka Bento - Faruqi, Muhammad Jill; Purnamasari, Pupung (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to examine promotional activities, the effect of price, and product quality on purchasing decisions in a fast foot hoka-hoka bento restaurant retail industry business developed by PT Fast Food Indonesia Tbk is the most visited fast food restaurant in Indonesia. This type of research is quantitative research. This study uses a measurement method that is carried out by filling out data in the form of a questionnaire using a Likert scale as a measurement model. This study uses a data analysis approach using computer media running SmartPLS version 3.0 software. PLS (Partial Least Squares) with a measurement model is used to assess validity, reliability, and model structure is used for causality testing (i.e. hypothesis testing using predictive models). This study found that there is a positive significant effect of promotion on Hoka-Hoka Bento consumer purchasing decisions, a positive significant effect of price on Hoka-Hoka Bento consumer purchasing decisions, a positive significant effect of product quality on Hoka-Hoka Bento consumer purchasing decisions, and a positive significant effect of promotion, price, and product quality on Hoka-Hoka Bento consumer purchasing decisions.